PERTUMBUHAN DAN HASIL DUA VERIETAS KEDELAI (Glycine max L.) DENGAN PEMBERIAN PUPUK HAYATI - Mahdiannoor Mahdiannoor; Nurul Istiqomah; Syahbudin Syahbudin (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Soybean is a much needed agricultural commodity in Indonesia. Soybean production in South Kalimantan in 2012 is 3,860 tons of dry weihgt (tDW), in 2013 4,072 tBK, in 2014 8,946 tDW, in 2015 10,537 tDW. Varieties play an important role in soybean production, because to achieve high yields are highly determined by genetic potential. Potential results in the field are influenced by the interaction between genetic factors with the management of climatic and soil environmental conditions. In podsolic soils and soils containing a lot of quartz sand, soybean growth is poor, unless the soil is given additional organic fertilizer. Bioertilizer is a fertilizer whose main content is living organisms (microorganisms) that are beneficial for plant growth. This study aims to (i) know the growth and yield of two soybean varieties with the provision of biological fertilizers (ii) to obtain the best soybean varieties with the provision of biofertilizer. The research was conducted in March - May 2017 at BPTP Experimental Plant of South Kalimantan Muara Rintis Village, District of Batang Alai Utara Regency of Hulu Sungai Tengah. The treatments were two varieties of soybean namely the national superior varieties (Anjosmoro) and local varieties given biological fertilizer. The result of research shows that all observation variables significantly affect with the best soybean varieties are Anjosmoro Varieties.